THE RELATIONSHIP BETWEEN SALTED FISH AND HYPERTENSION IN COASTAL AREAS: A SCOPING REVIEW: Hubungan Antara Ikan Asin dan Hipertensi di Wilayah Pesisir: Sebuah Tinjauan Cakupan - Aliyah, Ira Nur; Aditya Nugraha, Bambang; Ulfah Rifa'atul Fitri, Siti (Universitas Airlangga, 2026)
Background: Hypertension is a major public health issue worldwide, and its prevalence is higher in coastal areas with significant contribution from high dietary sodium such as salted fish. It is salted and dried fish that still BYs part of their daily diet in these parts, because of its very keeping-qualities and abundance. Purpose: The purpose was to systematically map the scientific evidence on the relationship among salted fish consumption and hypertension in coastal regions. Methods: A scoping review method was used in this study based on the PRISMA-ScR guidelines. PCC were perBYed on five databases including: PubMed, Scopus, Science Direct, Cambridge Core and Google Scholar using the PCC framework with key search terms;